KEKUATAN OTOT QUADRICEPS BERHUBUNGAN DENGAN QUALITY OF LIFE PASCA REKONSTRUKSI ANTERIOR CRUCIATE LIGAMENT - Ni Putu Aprilia Chintya Dewi (Masker Medika, 2024)
Abstract Background: After undergoing anterior cruciate ligament reconstruction, great quadriceps muscle strength can improve the rehabilitation process and quality of life. This study aimed to evaluate the long-term changes of post-reconstruction anterior cruciate ligament rehabilitation by understanding the extent to which quadriceps muscle strength and patient demographic factors correlate with quality of life components. Methods: This study used an observational analytic design with a cross-sectional study approach. Involving 26 ACLR patients from the Indonesian ACL Community in Bali. Quadriceps muscle strength was measured with a hand-held dynanometer, while quality of life was evaluated with the Short-form Health Survey 36 questionnaire. Results: The analysis showed a significant relationship between quadriceps muscle strength and quality of life in the aspects of physical limitations and vitality (p = 0.049 and p = 0.005; correlation coefficients 0.389 and 0.533). Patients with poor quadriceps muscle strength had a higher risk of physical limitation (1.20 times risk) and decreased vitality (16.5 times risk) compared to those with good muscle strength (p = 0.030 and p = 0.025). Discussion: Individuals who have undergone ACL reconstruction and have decreased quadriceps muscle strength will have decreased quality of life in the aspects of high levels of physical limitations and decreased vitality function.